Kedudukan Majelis Kehormatan Mahkamah Konstitusi Dalam Sistem Kelembagaan Di Indonesia - Moch. David Herdiansyah; Tahegga Primananda Alfath (Jurnal Hukum Saraswati (JHS), 2025)
This study analyzes the role and position of the Honorary Council of the Constitutional Court (MKMK) in maintaining the integrity and ethics of Constitutional Judges in Indonesia. Although MKMK has been legitimized through PMK Number 1 of 2023, in-depth studies on its position in the state institutional system are still limited. This research uses a normative approach with a focus on analyzing legislation and related legal concepts. The results show that MKMK acts as a quasi judicial body that handles violations of the code of ethics of constitutional judges, as well as a state support institution that supports supervision in the constitutional system. This research emphasizes the importance of a deeper understanding of the position of the MKMK to ensure its optimal function in accordance with the principles of the rule of law